PETROELECTRICAL MODEL OF RESERVOIR ROCKS FROM OF WEST-SHEBELINSKA GAS CONDENSATE FIELD - Vyzhva, S.; Onyshchuk, D.; Onyshchuk, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The features of technique and results of petroelectrical investigation of complex-structured terrigenous reservoir are considered. As well results of determination of electric data and their connection with capacity properties of sandstones and siltstones (mudstones) of one drilling interval of the Dniepr-Donetsk Basin are cited in this article. Their petroelectrical models are created.